2021
DOI: 10.1155/2021/9991808
|View full text |Cite
|
Sign up to set email alerts
|

CFD Numerical Investigation of a New Solar Flat Air-Collector Having Different Obstacles with Various Configurations and Arrangements

Abstract: This work deals with a numerical parametric optimization study of a new Solar Flat Air Collector (SFAC) configuration. The CFD numerical parametric study investigates various SFAC structures inside the air cavity without obstacles and with spherical, cubic, cylindrical, and pyramidal obstacles. The study optimizes the most convenient configuration and arrangement that allow for the increase of the heat-transfer surface and to make the flow homogeneous in order to generate turbulence zones inside the SFAC air c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…For solar air collectors, the average Nu is calculated by Eq. 7 (Choi H and Choi K 2020;Rouissi et al 2021 The percentage between the thermal power that is actually transferred to air and the maximum theoretical power is referred to as the thermal efficiency of SAC and can be written by Eq. 9 (Rouissi et al 2021): (9) where (Eq.…”
Section: Data Reduction and Grid Independencementioning
confidence: 99%
See 1 more Smart Citation
“…For solar air collectors, the average Nu is calculated by Eq. 7 (Choi H and Choi K 2020;Rouissi et al 2021 The percentage between the thermal power that is actually transferred to air and the maximum theoretical power is referred to as the thermal efficiency of SAC and can be written by Eq. 9 (Rouissi et al 2021): (9) where (Eq.…”
Section: Data Reduction and Grid Independencementioning
confidence: 99%
“…The following thermophysical properties, which hold true for temperature ranges between 280 and 470 K, will be incorporated into the present model for the accuracy of the simulation results (Eqs. 12-15)(Rouissi et al 2021):…”
mentioning
confidence: 99%
“…The governing equations considered in the present CFD analysis are based on the following Navier-Stokes equations [20,31,32]:…”
Section: Mathematical Expressions For Cfd Modellingmentioning
confidence: 99%
“…The authors found that the thermal efficiency increases continuously with an increase in fluid mass flow rate, whereas thermohydraulic efficiency increases up to an inception value of fluid mass flow rate, attains a maximum, and then decreases sharply for a given fin spacing and fin height. Also, considerable work has been done by Rouissi et al (2021). This study has focused on the effect of baffles and their orientation on the global thermal efficiency of the solar flat air collector.…”
Section: Introductionmentioning
confidence: 99%